Evaluation of child development: beyond the neuromotor aspect - Sophie Helena Eickmann; Alan Martin Emond; Marilia Lima (Elsevier, 2016)
Objective: To review the epidemiology and update the scientific knowledge on the problems of development and behavior in childhood, and the recommendations for the role of the pediatrician in identifying and managing delays and disturbances in child development and mental health. Sources: A search for relevant literature was performed in the PubMed and Scopus databases and publications of the National Scientific Council on the Developing Child. Summary of the findings: With the decline in the incidence of communicable diseases in children, problems with development, behavior, and emotional regulation are increasingly becoming a part of the work of pediatricians, yet many are not trained and feel uncomfortable about this extension of their role. The available screening tools for child development and behavior are reviewed, and a 'school readiness' checklist is presented, together with recommendations on how the pediatrician can incorporate developmental surveillance into routine practice, aware of the need for children to acquire social, emotional, and cognitive skills so that they can develop their full potential. Conclusions: The pediatrician's role in the future will include both physical and mental health, recognizing that social development, resilience, and emotional maturity are as important as physical growth and neuromotor skills in a child's life course. Resumo: Objetivo: Revisar a epidemiologia e atualizar os conhecimentos científicos sobre os problemas do desenvolvimento e do comportamento na infância, e das recomendações do papel do pediatra na identificação e conduta frente aos transtornos da saúde mental infantil. Fontes de dados: Pesquisamos a literatura relevante nas bases de dados PubMed e Scopus e em publicações do National Scientific Council on the Developing Child. Síntese dos dados: Com o declínio na incidência de doenças transmissíveis em crianças, problemas do desenvolvimento, comportamento e regulação emocional fazem cada vez mais parte do trabalho do pediatra, mas muitos ainda não estão treinados e se sentem desconfortáveis com essa extensão do seu papel. Os instrumentos de triagem do desenvolvimento e comportamento foram revisados e uma lista de verificação da 'prontidão escolar' foi apresentada, juntamente com orientações sobre como o pediatra pode incorporar a vigilância da saúde mental em sua de rotina de atendimento, consciente da necessidade da aquisição das habilidades sociais, emocionais e cognitivas para que a criança possa desenvolver toda sua potencialidade. Conclusões: O papel do pediatra no futuro irá abranger tanto a saúde física quanto a mental, reconhecendo que o desenvolvimento social, a resiliência e o amadurecimento emocional são tão importantes quanto o crescimento físico e habilidades neuromotoras no curso da vida de uma criança. Keywords: Child development, Mental health, Behavior disorders, Screening tests, Toxic stress, School readiness, Palavras-chave: Desenvolvimento infantil, Saúde mental, Distúrbios de comportamento, Testes de triagem, Estresse tóxico, Prontidão escolar